2014
DOI: 10.1287/orsc.2013.0880
|View full text |Cite
|
Sign up to set email alerts
|

Just Like a Woman? Effects of Gender-Biased Perceptions of Friendship Network Brokerage on Attributions and Performance

Abstract: D o women face bias in the social realm in which they are purported to excel? Across two different studies (one organizational and one comprising MBA teams), we examined whether the friendship networks around women tend to be systematically misperceived and whether there were effects of these misperceptions on the women themselves and their teammates. Thus, we investigated the possibility (hitherto neglected in the network literature) that biases in friendship networks are triggered not just by the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 78 publications
2
88
0
Order By: Relevance
“…We focus our account on a key dimension on which men's and women's construal of brokerage is likely to differ: the perceived potential for being negatively evaluated on the basis of one's gender. Building on previous research that suggests that open networks have masculine associations (Brands & Kilduff, 2013;Brands et al, 2015), we posit (and empirically establish) the existence of a negative stereotype about women's performance as brokers in friendship networks. We further suggest that awareness of this stereotype triggers in women, but not in men, anxiety about task performance and negative social evaluations, which serves to undermine women's ability to fully capitalize on the informational benefits of their networks.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…We focus our account on a key dimension on which men's and women's construal of brokerage is likely to differ: the perceived potential for being negatively evaluated on the basis of one's gender. Building on previous research that suggests that open networks have masculine associations (Brands & Kilduff, 2013;Brands et al, 2015), we posit (and empirically establish) the existence of a negative stereotype about women's performance as brokers in friendship networks. We further suggest that awareness of this stereotype triggers in women, but not in men, anxiety about task performance and negative social evaluations, which serves to undermine women's ability to fully capitalize on the informational benefits of their networks.…”
mentioning
confidence: 93%
“…Brokerage positions in friendship networks have been shown to enhance the performance of individuals in organizations (Mehra, Kilduff, & Brass, 2001), but there is also evidence suggesting that they benefit men more than women. For example, a study of managers in a leading hightechnology firm found that social networks rich in structural holes led to early promotions for men but delayed promotions for women (Burt, 1992: 145-166); and a different study of student teams in a MBA program showed that gendered stereotypes about brokerage in friendship networks damaged the reputation of women who were seen to occupy these roles (Brands & Kilduff, 2013).…”
mentioning
confidence: 99%
See 3 more Smart Citations